Rationality of antibiotics prescription on pneumonia patients at the Indonesia Air Force Center Hospital (RSPAU) Dr. Suhardi Hardjolukito, Yogyakarta - Burju Simanjuntak, Lamhot; Siswandi; Gugun Suhendra; Dewi Wulandari; Wulanria Nurfitrika; Weti Widayanti; Nurhasna Suhmita Sari; Ikhwan Dwi Wahyu Nugroho (Indonesian Journal of Pharmacology and Therapy, 2024)
Irrational antibiotic prescriptions on pneumonia patients is common in hospitals. This study aimed to evaluate the rationality of antibiotics prescription on pneumonia patients at the Indonesia Air Force Center Hospital (RSPAU) Dr. Suhardi Hardjolukito, Yogyakarta. It was a cross-sectional study using prescriptions for inpatients and outpatients suspected of community acquired pneumonia (CAP) submitted to the Medical Record Installation. All prescribed drugs, including their dosage, duration, route of administration, and demographic information of patients were extracted. The rationality of antibiotic use was then evaluated using the Gyssens and PCNE methods by assessing the antibiotic use with standard treatments based on the Clinical Pathway of RSPAU Dr. Suhardi Hardjolukito, Yogyakarta and the Guideline for the Use of Antibiotics of the Ministry of Health, Republic of Indonesia number 28 in 2021. A total of 124 pneumonia patient prescriptions were evaluated. The rationality of antibiotic prescriptions based on the Gyssens and PCNE criteria were 65.7% and 65.26%, respectively. The irrational of antibiotics based on the Gyssens method consisted of incomplete antibiotic prescription (2.90%), antibiotics not indicated (2.23%), medications prescribed cost more than substitute medications (8.20%), and less duration of medications (19.40%). Furthermore, the irrationality of antibiotics based on the PCNE method consisted of untreated symptoms or indications (8.33%), treatment issues related to cost-effectiveness (1.39%), too short duration of medications (23.61%), and incorrect medication administration or dosage interval timing (1.39%). In conclusion, in general, the antibiotics prescription on pneumonia patients at the RSPAU Dr. Suhardi Hardjolukito was rational. However, this rationality can still be improved.